Targeting the HGF/MET Axis in Cancer Therapy: Challenges in Resistance and Opportunities for Improvement - Huang, Xing; Li, Enliang; Shen, Hang; Wang, Xun; Tang, Tianyu; Zhang, Xiaozhen; Xu, Jian; Tang, Zengwei; Guo, Chengxiang; Bai, Xueli; Liang, Tingbo (Frontiers in Cell and Developmental Biology, 2020)
Among hundreds of thousands of signal receptors contributing to oncogenic activation, tumorigenesis, and metastasis, the hepatocyte growth factor (HGF) receptor, also called tyrosine kinase MET, is a promising target in cancer therapy as its axis is involved in several different cancer types. Additionally, it is associated with poor outcomes and involved in the development of therapeutic resistance. Several HGF/MET-neutralizing antibodies and MET kinase-specific small molecule inhibitors have been developed, resulting in some context-dependent progress in multiple cancer treatments. Nevertheless, the concomitant therapeutic resistance largely inhibits the translation of such targeted drug candidates into clinical application. Until now, numerous studies have been performed to understand the molecular, cellular, and upstream mechanisms that regulate HGF/MET-targeted drug resistance, further explore novel strategies to reduce the occurrence of resistance, and improve therapeutic efficacy after resistance. Intriguingly, emerging evidence has revealed that, in addition to its conventional function as an oncogene, the HGF/MET axis stands at the crossroads of tumor autophagy, immunity, and microenvironment. Based on current progress, this review summarizes the current challenges and simultaneously proposes future opportunities for HGF/MET targeting for therapeutic cancer interventions.